Theoretical Aspects of the Territorial Approach to Region and Supply Chain Management - A. P. Tyapukhin (Управленческое консультирование, 2021)
The territorial approach is the basic approach to a region management. At the same time, the “territory” component is the basis of the logistics complex used in Supply Chain Management. In this regard, a need is to clarify and supplement the theory and methodology of the territorial approach to the management of both the region and the supply chains.The subject of this study is the relationship between the regional authorities and the focus enterprise of the supply chain regarding the development of the territories and resources of the region on a mutually beneficial basis.The research methods are methods of analysis and synthesis, induction and deduction, as well as classification, and the tools are binary matrices that provide for the joint use of two classification attributes of the object under study and their dichotomies.The results of this study are the management principles by the competitiveness and sustainability of the management object; classifications of approaches to the management by the region and supply chains; of territories from the point of view of the focus enterprise of the supply chain and the region; the management decisions in the interaction of regions with the links of supply chains; the sequence of the formation of supply chains and the development of territories and resources of the region on the basis of the territorial approach and the relationship between them.The obtained results allow to reduce the costs and time for the development of territories and resources of the region by reducing the lost profits of the supply chain links due to their rational placement and increasing sustainability by achieving a synergistic effect both by the region and by the supply chains.